2002
DOI: 10.1139/x01-220
|View full text |Cite
|
Sign up to set email alerts
|

Growth and crown morphological responses of boreal conifer seedlings and saplings with contrasting shade tolerance to a gradient of light and height

Abstract: The effects of gradients in light levels and tree height on growth and crown attributes of six conifer species were studied in eastern and western Canada. Three conifers were studied in British Columbia (Abies lasiocarpa (Hook.) Nutt., Picea glauca (Moench) Voss × Picea engelmannii Parry ex Engelm., and Pinus contorta Dougl. ex Loud. var. latifolia Engelm.), and three in Quebec (Abies balsamea (L.) Mill., Picea glauca, and Pinus banksiana Lamb.). For several growth and morphological parameters, conifers reacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
133
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(148 citation statements)
references
References 41 publications
12
133
1
1
Order By: Relevance
“…Grassi, R. Giannini affected by light level [8]. Within the range of irradiance of our study, no significant relationships were found between RHG, ADR or LCR and sapling height (P > 0.05 in all cases).…”
contrasting
confidence: 59%
See 2 more Smart Citations
“…Grassi, R. Giannini affected by light level [8]. Within the range of irradiance of our study, no significant relationships were found between RHG, ADR or LCR and sapling height (P > 0.05 in all cases).…”
contrasting
confidence: 59%
“…Therefore, understanding how these traits vary in relation to interacting factors is important in order to promote and assure effectively natural regeneration [1]. Several studies have shown that the effect of light on crown, shoot and needle morphology differs among tree species, with shade-tolerant species typically showing greater morphological changes along a light gradient than do the more shade-intolerant species [4,7,8,12,33]. At the whole plant level, interspecific differences reflect alternative choices between height growth for future gain and investment for survival at present height [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understory light availability is a good proxy for predicting juvenile tree growth in complex structured northern latitude forests (e.g., Klinka et al, 1992;Chen, 1997;Wright et al, 1998;Coates and Burton, 1999;Drever and Lertzman, 2001;Claveau et al, 2002). SORTIE/BC can predict light levels after any type of partial cutting, and it can be easily parameterized for different forest ecosystems (Canham et al, 1994(Canham et al, , 1999Beaudet et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The 30% uniform partial cut created slightly more shaded conditions (Figs. 5 and 6), less favourable to increased growth among pre-established shade-tolerant conifers (Parent and Messier, 1995;Claveau et al, 2002). More shaded conditions might even compromise regeneration survival for some species (e.g., below 8% for white spruce: Lieffers and Stadt, 1994), especially among larger saplings (Kneeshaw et al, 2006).…”
Section: Management Implicationsmentioning
confidence: 99%